The Effect Of Online Customer Review And Rating Dimensions On Purchase Intention In Shopee - Alfira, Risa (International Journal of Science, Technology & Management, 2025)
This study aims to determine the effect of online customer reviews and online customer ratings on purchase intention partially or simultaneously on shopees. This research is a descriptive study using quantitative methods. This research was conducted from September 2020 to January 2021. The object of this research is Shopee. Data collection was obtained through distributing questionnaires to 400 respondents.The sampling technique using nonprobability sampling is a convenience sampling technique with a population that is all Shopee platform users. Analysis of this data using Multiple Linear Regression. The results of the study indicate that the two variables simultaneously influence higher online customer review participation.